Bridging the Gap between Interest Rates and Investments. Issue 4 (December 2014) - Zenner, Marc; Junek, Evan; Chivukula, Ram
<x xml:space="preserve">Abstract</x> The links between interest rates, cost of capital, hurdle rates, and capital allocation have been remarkably weak during the last few years. For instance, whereas the current yield on the World Government Bond Index is a paltry 1.2%, survey evidence suggests that the median reported investment hurdle rate of S&P 100 companies is as high as 18%. In this report, members of J.P Morgan's corporate finance advisory group explain why the cost of capital for most companies is unlikely to increase materially even if interest rates rise as projected. This suggests that companies have room to lower their hurdle rates. Moreover, as the authors argue, a reduction in hurdle rates is likely to be beneficial since excessively high hurdle rates can have the effect of reducing value by sacrificing profitable growth opportunities and increasing the firm's risk profile. The report concludes with a framework for corporate hurdle rates and capital allocation strategies designed to help companies make better investment decisions.